2021
DOI: 10.3889/oamjms.2021.7188
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CD 163 Tumor-Associated Macrophages and Colorectal-Cancer Stem Cell Markers

Abstract: BACKGROUND: Colorectal-cancer stem cells (CR-CSCs) represent a specific subpopulation of colorectal cancer (CRC) cells, which are characterized by the expression of CD133 and CD166. Tumor-associated macrophages (TAMs), found near CSCs may represent polarized macrophages, which are characterized by CD163 expression. In most tumors, TAMs may promote aggressive tumor development, leading to poor prognoses. AIM: The aim of this study was to determine whether any association exists between CD163 expression in TAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition to these common components, intestinal cells are also in close contact with a large population of microorganisms referred to as the gut microbiota [33]. Published research found that there is a relationship between the expression levels of CD163 in Tumor Associated Macrophages (TAM) and the expression levels of colorectal cancer stem cell markers (CD133 and CD166) [35]. There is also previous research that studied CD133 expression and its correlation with clinicopathological profile of CRC patients in Medan, Indonesia.…”
Section: Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…In addition to these common components, intestinal cells are also in close contact with a large population of microorganisms referred to as the gut microbiota [33]. Published research found that there is a relationship between the expression levels of CD163 in Tumor Associated Macrophages (TAM) and the expression levels of colorectal cancer stem cell markers (CD133 and CD166) [35]. There is also previous research that studied CD133 expression and its correlation with clinicopathological profile of CRC patients in Medan, Indonesia.…”
Section: Tumor Microenvironment (Tme)mentioning
confidence: 99%